Photodynamic therapy reduces cell viability, migration and triggers necroptosis in prostate tumor cells - de Melo Gomes, Laura Calazans; de Oliveira Cunha, Amanda Branquinho; Peixoto, Luiz Felipe Fernandes; Zanon, Renata Graciele; Botelho, Françoise Vasconcelos; Silva, Marcelo José Barbosa; Pinto-Fochi, Maria Etelvina; Góes, Rejane Maira [UNESP]; de Paoli, Flávia; Ribeiro, Daniele Lisboa (Springer Nature, 2023)
Prostate cancer is the most common cancer in American men, aside from skin cancer. As an alternative cancer treatment, photodynamic laser therapy (PDT) can be used to induce cell death. We evaluated the PDT effect, using methylene blue as a photosensitizer, in human prostate tumor cells (PC3). PC3 were subjected to four different conditions: DMEM (control); laser treatment (L—660 nm, 100 mW, 100 J.cm−2); methylene blue treatment (MB—25 μM, 30 min), and MB treatment followed by low-level red laser irradiation (MB-PDT). Groups were evaluated after 24 h. MB-PDT treatment reduced cell viability and migration. However, because MB-PDT did not significantly increase the levels of active caspase-3 and BCL-2, apoptosis was not the primary mode of cell death. MB-PDT, on the other hand, increased the acid compartment by 100% and the LC3 immunofluorescence (an autophagy marker) by 254%. Active MLKL level, a necroptosis marker, was higher in PC3 cells after MB-PDT treatment. Furthermore, MB-PDT resulted in oxidative stress due to a decrease in total antioxidant potential, catalase levels, and increased lipid peroxidation. According to these findings, MB-PDT therapy is effective at inducing oxidative stress and reducing PC3 cell viability. In such therapy, necroptosis is also an important mechanism of cell death triggered by autophagy. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Cell death; Methylene blue; Photodynamic therapy; Prostate cancer